2016
DOI: 10.1093/bjsw/bcw027
|View full text |Cite
|
Sign up to set email alerts
|

‘London calling’: The Experiences of International Social Work Recruits Working in London: Table 1

Abstract: This recruitment of International social workers (ISWs) in England has been primarily aimed at 'plugging the gaps' in the child protection services. This paper reports on one aspect of a qualitative research project investigating the post-arrival integration, professional practice and development of 'international social workers' i.e. SWs trained and qualified outside of the UK working in London and the Home Counties. Findings demonstrate that as well as being a challenging professional and work experience thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Social workers relocate to other countries to undertake professional practice and this phenomenon has recently become more common among the Anglophone countries, as some existing studies have demonstrated (Bartley and Beddoe, 2018; Beddoe et al, 2012; Brown et al, 2014; Hanna and Lyons, 2016; Hussein, 2020; Modderman et al, 2020). One of the reasons for this growth is that countries like the UK, Australia, New Zealand and Canada have a shared tradition of recruiting overseas educated social workers to fill their labour shortages (Modderman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Social workers relocate to other countries to undertake professional practice and this phenomenon has recently become more common among the Anglophone countries, as some existing studies have demonstrated (Bartley and Beddoe, 2018; Beddoe et al, 2012; Brown et al, 2014; Hanna and Lyons, 2016; Hussein, 2020; Modderman et al, 2020). One of the reasons for this growth is that countries like the UK, Australia, New Zealand and Canada have a shared tradition of recruiting overseas educated social workers to fill their labour shortages (Modderman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the document lists a number of agency responsibilities including to ensure the provision of effective induction, supervision, workload management and opportunities for continuing professional development (CPD). With the possible exception of the last, these are all factors mentioned in various studies as having a particular impact on the experiences (whether positive or negative) of transnational social workers (for example, Fouché et al, 2015;Hanna and Lyons, 2016;and chapters in this volume by Beddoe et al;Brown et al;and Walsh-Tapiata et al).…”
Section: Local and Universal Problems: Different Approaches And Organ...mentioning
confidence: 98%
“…The koru model: The stages of biculturation for foreign-trained social workers in Aotearoa New Zealand Introduction Like many professions, social work has experienced the impact of globalisation. This is demonstrated by social work being a profession very much "on the move", with various authors exploring the impact of an increasing transnational social work workforce (Bartley et al, 2011;Bartley & Beddoe, 2018;Hanna & Lyons, 2017;Modderman et al, 2020;Pullen-Sansfaçon et al, 2012). Many studies have explored the process of settlement or acculturation for migrants into new countries (Zapf, 1991).…”
Section: Qualitative Researchmentioning
confidence: 99%